2018
DOI: 10.1134/s0040577918050045
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Analysis of Multilump Solutions of the Kadomtsev–Petviashvili-I Equation

Abstract: Inspired by the works of Y. Ohta and J. Yang, one constructs the lumps solutions in the Kadomtsev-Petviashvili-(I) equation using the Grammian determinants. It is shown that the locations of peaks will depend on the real roots of Wronskian of the orthogonal polynomials for the asymptotic behaviors in some particular cases. Also, one can prove that all the locations of peaks are on a vertical line when time approaches -∞, and then they will be on a horizontal line when time approaches ∞, i.e., there is a rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
1
18
1
Order By: Relevance
“…The most general Grammian form of the multilump solutions of KP‐I was considered in Ref. 52. 3. Lump chains .…”
Section: The Grammian Form Of the τ‐Functionmentioning
confidence: 99%
“…The most general Grammian form of the multilump solutions of KP‐I was considered in Ref. 52. 3. Lump chains .…”
Section: The Grammian Form Of the τ‐Functionmentioning
confidence: 99%
“…Analytical expressions of higher-order lumps have been derived by a wide variety of methods before [10][11][12][13][14][15][16][17][18][19][20][21]. Gorshkov, et al [10] reported a second-order lump solution that describes the interaction and anomalous scattering of two lumps.…”
Section: Introductionmentioning
confidence: 99%
“…Gaillard [19] studied a special class of higher-order lump solutions and reported lump patterns such as triangles and pentagons at t = 0 when some internal parameters in such solutions get large. Chang [20] studied the large-time asymptotics of higher-order lumps and showed that, for some special solutions, all lumps are located on a vertical line in the (x, y) plane at large negative time but rotate to a horizontal line at large positive time. Ma [21] derived a fundamental lump solution which contains more free parameters; but that solution can be made equivalent to the original lump solution as reported in [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…(d) Several authors [13,10] have considered a more general choice for φ n such as φ n = D n k exp(iθ) with θ(k) same as before but D k := f (k)∂ k where f (k) is analytic. In such cases, it is possible to consider D k = ∂ z in terms of a (local) uniformizing variable z(k) with z (k) = 1/f (k) and an appropriate branch of its inverse k(z) to express θ(k(z)).…”
Section: Remarksmentioning
confidence: 99%